An efficient terminal voltage control for PEMFC based on an improved version of whale optimization algorithm - Yan Cao; Yiqing Li; Geng Zhang; Kittisak Jermsittiparsert; Maryam Nasseri (Energy Reports, 2020)
Recently, the application of the proton exchange membrane fuel cells (PEMFCs) is extensively increasing as a popular renewable energy source. PEMFCs need low temperature for the operation along with high power density and easy implementation ability. These characteristics turned them into the most interesting type of fuel cells. However, PEMFCs need a technique for keeping them in a desired operating point. This is an essential item, especially during the current variation. In this study, a new configuration is proposed for designing an optimal PEMFC system. Two-phase interleaved boost DC/DC converter is also utilized for increasing the output voltage terminal.~LQR optimal strategy is used for regulating the PEMFC. For improving the efficiency of the proposed LQR controller, a newly developed version of the whale optimization algorithm, called improved chaotic whale optimization algorithm is proposed. Simulation results of the proposed system are compared with different methods and the results showed that the proposed system has higher efficiency from the viewpoint of the current ripple and overshoot.
Keywords: 330; Parameter estimation; Chaotic; LQR; Proton exchange membrane fuel cell; Whale optimization algorithm